AL-ASY’ARY DAN PAHAM AHL AL-SUNNAH WA AL-JAMÂAH - Ahmad Mantiq Alimuddin (STAI Nurul Falah Airmolek, 2017)
A statement stated that al-Ash’ari holed up at home for fifteen days after doing theological dialogue with al-Juba’i, one of mu’taziliy followers , to diligently and correctively write mu’tazila teachings. This is a starting point for grow of Ash’ari’steaching where there ulama born to spread the teachings. So, the teachings were widespread in all parts of the world.